High-redshift JWST predictions from IllustrisTNG: dust modelling and galaxy luminosity functions. Issue 4 (16th January 2020) - Vogelsberger, Mark; Nelson, Dylan; Pillepich, Annalisa; Shen, Xuejian; Marinacci, Federico; Springel, Volker; Pakmor, Rüdiger; Tacchella, Sandro; Weinberger, Rainer; Torrey, Paul; Hernquist, Lars
ABSTRACT: The James Webb Space Telescope ( JWST ) promises to revolutionize our understanding of the early Universe, and contrasting its upcoming observations with predictions of the Λ cold dark matter model requires detailed theoretical forecasts. Here, we exploit the large dynamic range of the IllustrisTNG simulation suite, TNG50, TNG100, and TNG300, to derive multiband galaxy luminosity functions from z = 2 to z = 10. We put particular emphasis on the exploration of different dust attenuation models to determine galaxy luminosity functions for the rest-frame ultraviolet (UV), and apparent wide NIRCam bands. Our most detailed dust model is based on continuum Monte Carlo radiative transfer calculations employing observationally calibrated dust properties. This calibration results in constraints on the redshift evolution of the dust attenuation normalization and dust-to-metal ratios yielding a stronger redshift evolution of the attenuation normalization compared to most previous theoretical studies. Overall we find good agreement between the rest-frame UV luminosity functions and observational data for all redshifts, also beyond the regimes used for the dust model calibrations. Furthermore, we also recover the observed high-redshift ( z = 4–6) UV luminosity versus stellar mass relation, the H α versus star formation rate relation, and the H α luminosity function at z = 2. The bright end ( M UV > −19.5) cumulative galaxy number densities are consistent with observational data. For the F 200 W NIRCam band, we predict that JWST will detect ∼80 (∼200) galaxies with a signal-to-noise ratio of 10 (5) within the NIRCam field of view, $2.2× 2.2 \, {\rm arcmin}^{2}$, for a total exposure time of $10^5\, {\rm s}$ in the redshift range z = 8 ± 0.5. These numbers drop to ∼10 (∼40) for an exposure time of $10^4\, {\rm s}$ .